Assessment of municipal solid waste generation in Universiti Putra Malaysia and its potential for green energy production - Zulkifli, Ahmad Aiman; Mohd Yusoff, Mohd Zulkhairi; Abd Manaf, Latifah; Zakaria @ Mamat, Mohd Rafein; Roslan, Ahmad Muhaimin; Ariffin, Hidayah; Shirai, Yoshihito; Hassan, Mohd Ali (MDPI, 2019)
The global waste generation keeps increasing over the years and it requires innovative solutions to minimize its impacts on environmental quality and public health. A strategic plan must be ascertained to overcome the future challenges of Municipal solid waste (MSW) locally and globally. Universiti Putra Malaysia (UPM) coined an initiative to demonstrate a showcase pilot plant for green energy production from MSW. The data was obtained from the survey and actual sampling within the UPM compound shows that UPM has generated 5.0–7.0 t/d of MSW generated consist of 30–35% organic fraction. Restaurants are the main source of the organic fraction. Upon separation, the organic fractions were digested into biogas. At a maximum conversion of the organic fraction, 715 kWh of electricity might be generated from the 2.2 t/d of organic waste generated in UPM. In this study, organic components from UPM were proposed to be subsequently used as a substrate via anaerobic digestion to produce green energy in the form of electricity or flammable fuels.